2015
DOI: 10.3109/10903127.2015.1025157
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Trauma Triage Decision-making: A Model of What Happens between the 9-1-1 Call and the Hospital

Abstract: Objective We describe the decision-making process used by emergency medical services (EMS) providers in order to understand how: 1) injured patients are evaluated in the prehospital setting; 2) field triage criteria are applied in-practice; and 3) selection of a destination hospital is determined. Methods We conducted separate focus groups with advanced and basic life support providers from rural and urban/suburban regions. Four exploratory focus groups were conducted to identify overarching themes and five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
90
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 25 publications
5
90
0
Order By: Relevance
“…After removal of duplicates, a total of 362 abstracts and titles were reviewed and from that, the full text of 59 articles were further assessed resulting in six articles included in the final summary. One article (47) was quantitative using a Likert scale survey, while four articles utilised a qualitative approach (48)(49)(50)(51) with the remaining article mixed-methods (52). Of the qualitative articles a mixture of data collection was used including interviews (48)(49)(50)52), clinical scenarios (18,49), case study (51), questionnaire survey (47,52) and real-life observation (50).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removal of duplicates, a total of 362 abstracts and titles were reviewed and from that, the full text of 59 articles were further assessed resulting in six articles included in the final summary. One article (47) was quantitative using a Likert scale survey, while four articles utilised a qualitative approach (48)(49)(50)(51) with the remaining article mixed-methods (52). Of the qualitative articles a mixture of data collection was used including interviews (48)(49)(50)52), clinical scenarios (18,49), case study (51), questionnaire survey (47,52) and real-life observation (50).…”
Section: Resultsmentioning
confidence: 99%
“…This theme appeared across studies examining various types of settings seen in paramedic practice including mental illness (51), trauma triage and hospital destination choices (49), as well as during general paramedic practice (52). For example, Shaban (51) reported sub-conscious processes were a significant driving theme encompassing safety (patient and paramedic) in mental illness attendances, whereas Jones et al (48) reported its use where speed over accuracy was warranted in the setting of trauma amidst abundant time-sensitive pressures. Paramedics in Ryan and Halliwell (52) also reported making intuitive-driven decisions overall based on pattern recognition pulling from previous experience.…”
Section: I) Sub-conscious Versus Conscious Cognitive Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Andersen 25 showed that this model provides a schematic overview of reasoning in dual-process theory. Decision making in emergency medical services emphasizes speed; therefore, Jones et al 28 proposed a medical decision making model in emergency medical services to describe how patients are evaluated in prehospital care, triage is applied, and the destination hospital is determined. Fig.…”
Section: Clinical Decision Support Systems In Prehospital Carementioning
confidence: 99%
“…Little is known about the frequency with which children are transported to a hospital with higher‐level pediatric resources. Most prior research on destination decision‐making has focused on the identification of injured patients who need a trauma center . However, transport to hospitals with higher‐level pediatric resources can be just as important for patients with medical‐related complaints as it is for trauma‐related complaints.…”
mentioning
confidence: 99%